Bibliometrik Systematic Literature Review: Heat Flux and Its Relation to Sea Surface Temperature Variability - Nuryadi, Ari; Wahyuni, Siltia (Universitas Negeri Padang, 2024)
Research on atmospheric properties and structure and air quality has become a topic of increasing interest due to the increasing impacts of climate change and environmental degradation. This study aims to analyze publication and citation trends related to atmospheric topics from 2014 to 2024, with a focus on the distribution of research topics, country contributions, and journal sources. Bibliometric analysis was conducted using the Scopus database with the Publish or Perish application, to identify publication patterns, productivity growth, and a significant decrease in the number of citations after 2020. The results show that China and the United States are the main contributors to the number of atmospheric publications, with topics dominated by air pollution emissions and changes in atmospheric chemical composition. However, since 2020, there has been a sharp decline in productivity and citations that coincides with changes in global scientific policies and priorities. These findings provide important insights into the dynamics of atmospheric research, and suggest the need for new strategies to maintain the relevance and sustainability of research in this field. This study is expected to contribute to steering atmospheric research in a direction that is more responsive to global environmental challenges.